Pengaruh Profitabilitas Dan Likuiditas Terhadap Nilai Perusahaan Pada Perusahaan Sub Sektor Transportasi Yang Terdaftar Di BEI Di Masa Pandemi Covid-19 - Fakhrurrazi Fakhrurrazi; Dessi Susanti (Universitas Negeri Padang, 2023)
The objective of this study is to see how profitability affects firm value in transportation sub-sector companies listed on the IDX during the Covid-19 pandemic, as well as how liquidity affects firm value in transportation sub-sector companies listed on the IDX during the Covid-19 pandemic. This is referred to as comparative causal research. The population of this study consists of transportation sub-sector companies listed on the IDX in 2019-2020. The sample size for this study was 13 businesses. Purposive sampling was used in the sampling technique. Profitability is measured by Return on Equity (ROE), liquidity by Current Ratio (CR), and firm value by Price to Book Value (PBV) (PBV). The data analysis technique employs panel data analysis with the Eviews 9 software. The study's findings show that profitability and liquidity both have an impact on firm value. Profitability has a marginally negative impact on firm value. Liquidity has a marginally insignificant effect on firm value.